2021
DOI: 10.1186/s13018-021-02704-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of posterior tibial slope on the mid-term clinical effect of medial-pivot knee prosthesis

Abstract: Objective To evaluate the effect of posterior tibial slope (PTS) on the mid-term clinical outcome following a medial-pivot (MP) prosthesis. Method Two hundred thirty-three patients from The Affiliated Hospital of Qingdao University, who had undergone a total knee arthroplasty (TKA) with MP prosthesis between January 2015 and December 2015, were retrospectively included in this study. They were divided into 3 groups according to postoperative PTS: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It is generally believed that knees with a greater tibial slope have greater knee flexion [ 16 , 17 ]. Although many articles in the literature found a correlation between the increase in PTS and maximal flexion, we could not find a relationship between PTS and maximal flexion in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that knees with a greater tibial slope have greater knee flexion [ 16 , 17 ]. Although many articles in the literature found a correlation between the increase in PTS and maximal flexion, we could not find a relationship between PTS and maximal flexion in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Single ankle replacement for knee joint single compartment osteoarthritis has been favored by the majority of knee surgeons because of its obvious advantages and characteristics, such as less surgical trauma, short operation time and hospital stay, low hospitalization cost, satisfactory short-term effect, and so on. Riddle et al reported that the number of American condylar knee prosthesis replacement increased by an average of 32.5% per year from 1998 to 2005 [ 23 ]. More and more researchers have believed that condylar knee arthroplasty can relieve pain and improve the quality of life of patients with osteoarthritis in single compartment, especially in medial compartment [ 24 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because the long radiograph is often used in more difficult cases, LSKRs are frequently used in daily clinical practice during postoperative follow-up periods because of logistical and technical problems [ 7 ], convenience, and lower cost [ 8 ]. Even recent studies [ 9 , 10 ] have evaluated the PTS after TKA using LSKR. However, the PTS using LSKR should be regarded as the estimation of the true PTS using FLTR as LSKR without the ankle plafond cannot determine the mechanical axis of the tibia.…”
Section: Introductionmentioning
confidence: 99%